2012
DOI: 10.1016/j.ajpath.2011.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against Muscle-Specific Kinase Impair Both Presynaptic and Postsynaptic Functions in a Murine Model of Myasthenia Gravis

Abstract: Antibodies against acetylcholine receptors (AChRs) cause pathogenicity in myasthenia gravis (MG) patients through complement pathway-mediated destruction of postsynaptic membranes at neuromuscular junctions (NMJs). However, antibodies against muscle-specific kinase (MuSK), which constitute a major subclass of antibodies found in MG patients, do not activate the complement pathway. To investigate the pathophysiology of MuSK-MG and establish an experimental autoimmune MG (EAMG) model, we injected MuSK protein in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
134
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(155 citation statements)
references
References 55 publications
13
134
0
8
Order By: Relevance
“…Animal experiments show that MuSK immunoglobulin G (IgG) can cause MG. Mice that received repeated daily injections of patient IgG showed impaired neuromuscular transmission, with reductions in endplate AChR [18][19][20]. Similar changes to endplates were reported in mice, rats, and rabbits that were actively immunized with MuSK [21,22].…”
Section: Krisnamurti Et Alsupporting
confidence: 59%
“…Animal experiments show that MuSK immunoglobulin G (IgG) can cause MG. Mice that received repeated daily injections of patient IgG showed impaired neuromuscular transmission, with reductions in endplate AChR [18][19][20]. Similar changes to endplates were reported in mice, rats, and rabbits that were actively immunized with MuSK [21,22].…”
Section: Krisnamurti Et Alsupporting
confidence: 59%
“…An increase in quantal content, however, is not evident in MuSK MG (12,16,45). These findings suggest that MuSK plays an important role in this homeostatic response.…”
Section: Discussionmentioning
confidence: 51%
“…These studies have shown that bivalent MuSK antibodies activate MuSK phosphorylation and inhibit Agrindependent AChR clustering (16,36), whereas monovalent Fab fragments, generated from these antibodies, inhibit MuSK phosphorylation and AChR clustering (37). Because rabbits lack the equivalent of human IgG4 antibodies, and mouse IgG binds complement (38,39), the active immunization models lead to the production of classic, bivalent antibodies that cross-link antigens, deplete cell-surface expression, and engage complement.…”
Section: Discussionmentioning
confidence: 99%
“…Ecto-LRP4 was emulsified with CFA and injected into female A/J mice, a strain that has been used successfully to establish MuSK EAMG (33,36). Mice received 3 boost injections (at weeks 4, 7, and 16) with ecto-LRP4 emulsified with incomplete Freund adjuvant (IFA); control mice were injected with emulsified PBS.…”
Section: Immunization With Lrp4 Extracellular Domain Causes Muscle Wementioning
confidence: 99%
“…Approximately 40%-70% of seronegative patients have antibodies against MuSK (28)(29)(30). Immunization with the extracellular domain of MuSK causes MG in rodents and rabbits (31)(32)(33)(34)(35)(36). Passive transfer of IgG from antiMuSK-positive MG patients causes MG in adult animals (37)(38)(39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%